Light it, shoot it, retouch it : learn it all, from lighting with flash, to the camera settings and gear, to retouching in Lightroom and Photoshop - Kelby, Scott (Rocky Nook, 2023)
Learn all three aspects of what it takes to create stunning portraits--lighting, shooting, and retouching! Scott Kelby, the world's #1 best-selling author of photography techniques books, has reinvented how lighting books are written by revealing the entire process from start to finish, all in this one book. In this fully revised and updated edition of his smash best-selling book Light It, Shoot It, Retouch It, you'll see everything from the complete lighting setup (and all the gear used), to the shoot (including all the camera settings and a contact sheet of the progression of the shoot), to the all-important part that most books don't dare include-the post-processing and retouching in Lightroom and Photoshop. This book also breaks new ground in the visual way that Scott teaches you the lighting setups. There aren't any sketches or 3D models-you see the actual lighting layout in photos taken during the live shoot. You'll see angles from above, to the side, and every other helpful perspective you may need, while also showing the exact distances between the light and the subject and the background. You name it--you see it all. Plus, you get additional behind-the-scenes views so you can be confident that you'll absolutely nail the lighting every time. Throughout the book, Scott uses speedlights/flash for all of the lighting techniques. So whether you use flashes or studio strobes, the book will work for you. You'll learn: ⁰́Ø The step-by-step layouts for creating the most-requested and sought-after lighting looks ⁰́Ø How to get more out of one light than you ever thought you could (this is worth buying the book alone!) ⁰́Ø How to control and shape your light without breaking the bank ⁰́Ø The camera settings, gear, and power settings for every shot ⁰́Ø The retouching techniques the pros really use to make their subjects look their very best ⁰́Ø How to retouch hair, eyes, lips, skin, and lots of other little retouching tricks that make a really big difference ⁰́Ø How to create high-contrast portrait effects without buying expensive plug-ins ⁰́Ø A host of insider tricks, invaluable shortcuts, and jaw-dropping special effects to give you a real advantage over the competition.